A triclinic crystal structure of the carboxy‐terminal domain of HIV‐1 capsid protein with four molecules in the asymmetric unit reveals a novel packing interface. Issue 6 (31st May 2013) - Lampel, Ayala; Yaniv, Oren; Berger, Or; Bacharach, Eran; Gazit, Ehud; Frolow, Felix
<x xml:space="preserve">Abstract</x> The Gag precursor is the major structural protein of the virion of human immunodeficiency virus‐1 (HIV‐1). Capsid protein (CA), a cleavage product of Gag, plays an essential role in virus assembly both in Gag‐precursor multimerization and in capsid core formation. The carboxy‐terminal domain (CTD) of CA contains 20 residues that are highly conserved across retroviruses and constitute the major homology region (MHR). Genetic evidence implies a role for the MHR in interactions between Gag precursors during the assembly of the virus, but the structural basis for this role remains elusive. This paper describes a novel triclinic structure of the HIV‐1 CA CTD at 1.6 Å resolution with two canonical dimers of CA CTD in the asymmetric unit. The canonical dimers form a newly identified packing interface where interactions of four conserved MHR residues take place. This is the first structural indication that these MHR residues participate in the putative CTD–CTD interactions. These findings suggest that the molecules forming this novel interface resemble an intermediate structure that participates in the early steps of HIV‐1 assembly. This interface may therefore provide a novel target for antiviral drugs.